The Atlas Underground flood [compact disc] - Morello, Tom, 1964- (Mom+Pop, 2021)
Featuring a jaw-dropping cast of collaborators, Tom Morello's album is the follow-up to the Rage Against The Machine guitarist's groundbreaking 2018 album The Atlas Underground and 2021 album The Atlas Underground Fire. Morello's insane guitar playing is on full display, taking the instrument into the future and forging an alternative/rock/EDM masterpiece with all-time legends and cutting-edge firebrands.